Design and evaluation of a hypoallergenic peptide-based vaccine for Salsola kali allergy - Tabesh, Saeideh; Fanuel, Songwe; Fazlollahi, Mohammad Reza; Yekaninejad, Mir Saeed; Kardar, Gholam Ali; Razavi, Seyed Alireza (Elsevier, 2022)
Background: The Salsola kali (S. kali) pollen is one of the most important causes of allergic rhinitis in the deserts and semi-desert areas. Immunotherapy with allergen extracts remains the only available treatment addressing the underlying mechanism of allergy. However, given the low efficacy of this method, it is necessary to find more effective and alternative therapeutic interventions using molecular biology and bioinformatics tools. In this study, a hypoallergenic vaccine was designed on the basis of B-cell epitope approach for S. kali immunotherapy. Methods: Using the Immune Epitope Database (IEDB), a 35-mer peptide was selected and chemically conjugated to a keyhole limpet hemocyanin (KLH) molecule. Specific IgG and IgE from immunized BALB/c mice sera against the vaccine (Sal k 1-KLH), S. kali extract and the recombinant protein, rSal k 1, were measured using ELISA. Also, inhibition of IgE by mouse IgG was evaluated using an inhibitory ELISA. Finally, the IgE reactivity and T-cell reactivity of the designed vaccine were evaluated by dot blot assay and MTT assay. Results: Vaccination with the vaccine produced high levels of protective IgG in mice, which inhibited the binding of patients IgE to recombinant proteins. The result showed that the designed vaccine, unlike the recombinant protein and extract, did not induce T-cell lymphocytes response and also exhibited decreased IgE reactivity. Conclusion: The designed vaccine can be considered as a promising candidate for therapeutic allergen-specific immunotherapy.